Analytical Method of Multi-Mycotoxins in Table-Ready Foods for a Total Diet Study Using Stable Isotope Dilution Liquid Chromatography–Tandem Mass Spectrometry. (3rd December 2019) - Lee, Youngsun; Kim, Jung Hee; You, Da-Jung; Kim, Cho-Il; Lee, Jee-Yeon; Park, Hyun-Mee
Abstract: Background: Determining the multi-mycotoxins present in table-ready foods is necessary for a total diet study. However, so far, most methods of analyzing multi-mycotoxins apply to raw foods. Therefore, a reliable method for analyzing multi-mycotoxins in table-ready foods is needed. Objective: We developed and validated methods of multi-mycotoxin analysis that employed stable isotope dilution with LC–tandem MS (LC–MS/MS) using two representative matrices. Methods: Samples were fortified with [ 13 C]-labeled mycotoxins as internal standards and extracted with 50% acetonitrile in water for high-carbohydrate foods and 3% formic acid in acetonitrile for high-protein and/or high-fat foods, cleaned up with n -hexane and the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method, and followed up by LC–MS/MS. Results: Validation of the methods was performed, and the results were as follows: the correlation coefficient, R 2, was 0.99; method detection limit, 0.01–2.4 μg/kg; recoveries, 83.6–114%; precision, 0.8–10 (intraday) and 3.1–22% (interday); interlaboratory reproducibility, ≤15%; and uncertainty, 3.5–19%error . The applicability of the methods was evaluated by analyzing table-ready foods spiked with standards. Conclusions: These methods were successfully evaluated and deemed appropriate for determining the multi-mycotoxins in table-ready foods. Highlights: This work demonstrates that stable isotope dilution with LC–MS/MS can be effectively used to analyze multi-mycotoxins simultaneously in a total diet study.